A coincidence theory involving Fredholm operators of nonnegative index - Gabor, Dorota; Kryszewski, Wojciech (Topological Methods in Nonlinear Analysis, 2000)
We construct a homotopy invariant appropriate for studying the existence of coincidence points of Fredholm operators of nonnegative index and multivalued admissible maps. Cohomotopy methods are used as a more suitable tool than homological ones. Both finite and infinite dimensional cases are investigated.